Britain and the British Antarctic Territory in the wider geopolitics of the Antarctic and the Southern Ocean. (November 2013) - DODDS, KLAUS; HEMMINGS, ALAN D.
Abstract : Britain's contemporary and future relationship with the British Antarctic Territory and the wider region is the subject matter of this article. In the aftermath of the ill‐fated plans for a merger of British Antarctic Survey (BAS) and the National Oceanography Centre, it is timely to ask how the UK projects influence and secures its scientific, resource and strategic interests. The contemporary Antarctic is increasingly characterized by tension over resource management and conservation politics as Antarctic Treaty parties disagree, both in private and public, over the purpose of legal instruments and the regulation of activities such as fishing and marine conservation. While we do not predict the collapse of the Antarctic Treaty System (ATS), our analysis suggests that the effectiveness and legitimacy of the ATS is increasingly under challenge. The United Kingdom's position as a claimant state and original signatory to the Antarctic Treaty is complicated by the presence of counter‐claimants (Argentina and Chile) and a wider preoccupation with other overseas territories, such as South Georgia and South Sandwich Islands and the Falkland Islands. Polar science, carried out by BAS and other British agents, remains critical not only for maintaining the UK's 'soft power' but also increasingly for cementing a 'strategic presence' in the Antarctic. The article ends with a cautionary note: scientific excellence is no longer sufficient to guarantee geopolitical/strategic interests and there is growing evidence that claimant and non‐claimant states alike are no longer regarding Antarctica as an area that will remain free of intensifying and diversifying resource exploitation.